Maximizing profits: How productivity drives success in personal care companies - Puspitasari, Adelya; Cahyaningsih, Diyah Sukanti; Suprapti, Suprapti; Lisetyati, Eni (University of Merdeka Malang, 2024)
This research aims to analyze the effect of productivity on Return on Equity (ROE) in personal care products subsector companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. Productivity in this research is measured using the ratio of EBIT to Total Production Costs, while asset use efficiency is measured using Total Asset Turnover (TATO). The data used in this research were obtained from the annual financial reports of companies included in the personal care products subsector. The analytical method used is multiple linear regression to test the effect of productivity and TATO on ROE. The research results show that productivity as measured by the ratio of EBIT to Total Production Costs does not have a significant influence on ROE. Meanwhile, TATO shows a significant influence on ROE in the companies studied. These findings indicate that in the personal care products subsector, asset use efficiency has an influence on ROE. However, considering that the R2 value is less than 50%, it is very important to consider that factors such as marketing strategy, product innovation, and cost management may play a more dominant role in determining a company's financial performance. This research provides insight for company management and investors about the importance of considering various factors that influence profitability and overall financial performance. It is recommended for further research to expand the independent variables studied and consider external conditions that can influence research results.